Perencanaan Kurikulum Perguruan Tinggi di era Industri 4.0 - Asnawi, Asnawi; Rahmawati, Nur Laila (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2024)
Universities are the main pillars in preparing competent human resources ready to face the changing times, especially in the era of Industry 4.0 characterized by digital and technological revolutions. In this context, curriculum planning becomes crucial to ensure the relevance of education with the demands of industries and society. The aim of this research is to analyze Curriculum Planning in Higher Education in the era of Industry 4.0. This research method utilizes a qualitative approach, specifically a case study research type. The findings of this research include: (1) Universities face challenges in adapting their curricula to the rapid developments in technology and changing demands of industries. (2) The findings also highlight the importance of collaboration between universities, industries, government, and society to ensure the responsiveness and relevance of university curricula to the rapidly changing industrial needs. (3) The discussion emphasizes the need for reform in the structure of higher education and academic culture to facilitate innovation in curriculum planning. Thus, the results and discussions of this research provide in-depth insights into the challenges, opportunities, and practical guidance for universities in designing curricula that are responsive and relevant to the era of Industry 4.0.